PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VIIIa MTsN PANGEAN - Wiwin Crisdayanti; Sakur '; Rini Dian Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students achievement in learning mathematics especially grade VIIIa of MTsN Pangean under the Mastery Minimum Criteria with percentage of20%on the test about The equation Linier Two Variables. This research is a class action research. This research aims to improve the learning process and improve learning result in mathematicswith applied of the model learning cooperative type of Student Team Achievement Division (STAD). The subject of this research were the students in the class VIIIa of MTsNpangean at the second semester of academic year 2016/2017that consist of 16girls and 9boys.The instruments of data collection in this research were observation sheets and student’s mathematic tests. The observation sheets were analyzed in desciptive narative, while the student’s mathematic tests were analyzed in statistic desciptive.The descriptive narative showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 20% to 24% on the first test and 44% on second test.On the analysis of KKM achievement, thestudents math achievement has increased from the base score to cycle I and cycle II. Based on the result of this research could be concluded that the implementation of cooperative learning with the application of the cooperative type STAD can improve the student’s achievement of learning mathematic in grade VIIIa of MTsN Pangean in the second semester of academic year 2016/2017.Keyword: Students Math Achievement, Cooperative Learning, The Type Student Team Achievement Division,Classroom Action Research.